If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + -1(-3) = x Multiply -1 * -3 -1 + 3 = x Combine like terms: -1 + 3 = 2 2 = x Solving 2 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + -1x = x + -1x Combine like terms: x + -1x = 0 2 + -1x = 0 Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| 1-(-3)=x | | 2(3x+5)=26-(6-3x) | | 2b+3b-5=5 | | 4x-12x^2=256 | | 2.7x+45.8=13.2-13.6x | | sin(4x)=-cos(2x) | | y=0.90x+116 | | .05x+.09(3x+20000)=49480 | | .4xy-2=6 | | 7+17t-16t^2=0 | | 2=-4(-2)+2 | | 6x-3y=-2 | | 2x=-4(-2)+2 | | y-(-9)=8/9(x-3) | | 7x^2+37x-30= | | 4-2(7p+4)=-88 | | 2x=-4(0)+2 | | y=80+6*2000 | | 7x^2-19x=-2x^2-5x-5 | | y=80+6*1000 | | 2x=-4(2)+2 | | 2000=80+6x | | 6*-4x=30 | | 6000=80+6x | | 1000=80+6x | | =80+6x | | .3(15d+3c)-.5(8c-10d)= | | -5-12+z=3+4z-3+2z | | 8/5(-0.6)(5/8) | | =2-4x+4*2+5*3 | | =2-3*9.333+4*2+5*3 | | 4b+3=8b-1+5b |